Transformational Leadership of the Principal in Achieving Success in the National Selection Based on Achievement - Setyawati; Maya Novita Sari (Journal of Education and Teaching Learning, 2026)
This study explores the role of transformational leadership in supporting the success of the National Selection Based on Achievement (SNBP) at SMAN 1 Bagan Sinembah, Rokan Hilir Regency. Using a qualitative case study design, data were collected through in-depth interviews, participant observation, and document study involving school leaders, curriculum staff, quality assurance personnel, teachers, and alumni. The findings show that the principal's transformational leadership was manifested through inspirational motivation, individualized consideration, and intellectual stimulation. Strategic practices included strengthening a shared vision, longitudinal analysis of student achievement, early class-package planning, layered PDSS verification, holiday tutoring, and data-based study-program rationalization. SNBP graduation increased from 11 students in 2018/2019 to 61 students in 2021/2022 and remained the highest at the regency level despite policy changes. The study concludes that transformational leadership can act as a catalyst for collective self-efficacy and school competitiveness when supported by systematic data management and collaborative teamwork.